PENGARUH LINGKUNGAN TEMAN SEBAYA, DISIPLIN BELAJAR DAN PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA PADA KELAS VII PADA MATA PELAJARAN IPS DI SMP TRI BHAKTI PEKANBARU TAHUN AJARAN 2018/2019 - Ermita Rihanda Dachi; Suarman Suarman; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of peer environment (X1), learning discipline (X2) and parental attention (X3) on learning achievement (Y) in class VII in the IPS lessons at SMP Tri Bhakti Pekanbaru Academic Year 2018/2019. This study took the entire population as a sample, namely students of class VII with a total of 97 respondents. This research is a quantitative descriptive with a kolerasional approach and uses the analysis method of multiple linear regression equations. Based on the results of the study, it can be known that the environment of peers is in good category, for the discipline of learning students in general are in good category and for the attention of parents also in good category. Furthermore, from the data analysis, it was found that the peer environment has a significant effect on student achievement, for learning discipline has a significant effect on learning achievement and for parental attention also significantly affects learning achievement with a contribution of 67.2% while the remaining 32,8% is determined by other factors such as study habits, learning attitudes, learning motivation and so on. This means that students who have a good peer environment allow the student to have good achievement, students who have good learning discipline will also have better learning achievement and students who have good parental attention allowing the student to have good learning achievement. .Keywords: Peer Friend Environment, Learning Discipline, Parental Attention, LearningAchievement.